THE THE EFFECTIVNESS OF MULLIGAN MOBILIZATION AND INFRARED WITH MYOFASCIAL RELEASE TECHNIQUE AND INFRARED TO IMPROVE RANGE OF MOTION OF NON-SPESIFIC NECK PAIN ON TAILOR IN THE SUBDISTRIC KUTA - Wahyuningsih, Ni Wayan; Wahyuni, Nila; Adiputra, Luh Made Indah Sri Handari (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 2 (2017): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT   Non-spesific neck pain is one of disorder among general population including tailors in Subdistric Kuta. Therefore the need for a therapy that can be given as myofascial release technique, mulligan mobilization, dan infrared. The design of this study was experimental with pre-test and post-test group design. The technique sampling was purposive sampling technique. The samples were divided into 2 groups. Group 1 was given Myofascial Release Technique and Infrared, while Group 2 was given Mulligan Mobilization and Infrared. The range of motion is measured by goniometer. The result showed no significant difference between Group 1 and Group 2 in which p value = 0.250 (p>0.05) with 56.8% in the Group 1 and 60.8% in the Group 2. Based on the result, it can be concluded that Myofascial Release Technique and Infrared show no significant difference with Mulligan Mobilization and Infrared to increase range of motion of the neck on the non-spesific neck pain.   Keywords : non-spesific neck pain, myofascial release technique, mulligan mobilization, infrared.